PENGARUH IKLAN DI MEDIA SOSIAL DAN ELECTRONIC WORD OF MOUTH TERHADAP BRAND IMAGE DALAM KEPUTUSAN PEMBELIAN (STUDI KASUS RS. BSH BOGOR) - Fadlin Rahmah; Selamet Riyadi (Journal of Innovation Research and Knowledge, 2025)
This study aims to analyze the influence of social media advertising and electronic word of mouth (e-WOM) on purchasing decisions for healthcare services, with brand image as an intervening variable at Bogor Senior Hospital (RS BSH). The approach used is quantitative with a descriptive causal method. Data was collected through a Google Form questionnaire distributed to 103 respondents who had been exposed to RS BSH advertisements on social media and had made repeat visits (cross-selling). Data analysis was conducted using SPSS software to test the relationships between research variables. The study results show that social media advertising does not significantly affect brand image or healthcare service purchasing decisions. In contrast, e-WOM has a positive and significant influence on both brand image and patient purchasing decisions. Furthermore, brand image is proven to mediate the relationship between e-WOM and purchasing decisions but does not mediate the relationship between social media advertising and purchasing decisions. These findings indicate that e-WOM plays a more dominant role in building brand image and influencing purchasing decisions than social media advertising. Therefore, RS BSH is advised to focus more on e-WOM-based marketing strategies, such as patient testimonials and online reviews, to enhance the hospital’s image and attract more patients